Philipp van Limborch and John Locke. The Arminian Influence on Locke’s Theology and Theory of Toleration - Svensson, Manfred (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
The aim of this essay is to present an analysis of the way in which the principal theologicalwork of Dutch Arminianism of seventeenth-century, Theologia Christiana of Philipp van Limborchinfluenced John Locke. The aim is two fold: to show, on the one hand, the influence of van Limborch’stheology on Locke’s theological reflections, on the other hand, the way in which Locke’s understandingof tolerance is embedded in this kind of theology.